Mechanochemical Knoevenagel condensation investigated in situ - Haferkamp, Sebastian; Fischer, Franziska; Kraus, Werner; Emmerling, Franziska (Beilstein Journal of Organic Chemistry, 2017)
The mechanochemical Knoevenagel condensation of malononitrile with p-nitrobenzaldehyde was studied in situ using a tandem approach. X-ray diffraction and Raman spectroscopy were combined to yield time-resolved information on the milling process. Under solvent-free conditions, the reaction leads to a quantitative conversion to p-nitrobenzylidenemalononitrile within 50 minutes. The in situ data indicate that the process is fast and proceeds under a direct conversion. After stopping the milling process, the reaction continues until complete conversion. The continuous and the stopped milling process both result in crystalline products suitable for single crystal X-ray diffraction.
Keywords: ball milling; C–C coupling; in situ; Knoevenagel condensation; mechanochemistry

(untitled) - Boldyreva, E. (Chem. Soc. Rev., 2013)

Encyclopedia of Physical Organic Chemistry - Kaupp, G. (2005)

(untitled) - James, S. L.; Adams, C. J.; Bolm, C.; Braga, D.; Collier, P.; Friščić, T.; Grepioni, F.; Harris, K. D. M.; Hyett, G.; Jones, W.; Krebs, A.; Mack, J.; et al. (Chem. Soc. Rev., 2012)

(untitled) - Sarkar, A.; Santra, S.; Kundu, S. K.; Hajra, A.; Zyryanov, G. V.; Chupakhin, O. N.; Charushin, V. N.; Majee, A. (Green Chem., 2016)

(untitled) - Walsh, P. J.; Li, H.; de Parrodi, C. A. (Chem. Rev., 2007)

(untitled) - Martins, M. A. P.; Frizzo, C. P.; Moreira, D. N.; Buriol, L.; Machado, P. (Chem. Rev., 2009)

Pharmaceutical salts and co-crystals - Wouters, J.; Quéré, L. (Royal Society of Chemistry, 2011)

(untitled) - Trask, A. V.; Motherwell, W. D. S.; Jones, W. (Int. J. Pharm., 2006)

(untitled) - Friščić, T.; Jones, W. (Cryst. Growth Des., 2009)

(untitled) - Karki, S.; Friščić, T.; Jones, W. (CrystEngComm, 2009)

(untitled) - Stolle, A.; Szuppa, T.; Leonhardt, S. E. S.; Ondruschka, B. (Chem. Soc. Rev., 2011)

(untitled) - Zhang, W.; Lu, L.; Cheng, Y.; Xu, N.; Pan, L.; Lin, Q.; Wang, Y. (Green Chem., 2011)

(untitled) - Friščić, T. (Chem. Soc. Rev., 2012)

(untitled) - Trask, A. V.; van de Streek, J.; Motherwell, W. D. S.; Jones, W. (Cryst. Growth Des., 2005)

(untitled) - Hernández, J. G.; Bolm, C. (J. Org. Chem., 2017)

Solvent-free organic synthesis - Tanaka, K.; Kaupp, G. (John Wiley & Sons, 2009)

(untitled) - Kaupp, G. (CrystEngComm, 2009)

(untitled) - Rodríguez, B.; Bruckmann, A.; Rantanen, T.; Bolm, C. (Adv. Synth. Catal., 2007)

(untitled) - Wang, G.-W. (Chem. Soc. Rev., 2013)

(untitled) - Toda, F.; Tanaka, K.; Hamai, K. (J. Chem. Soc., Perkin Trans. 1, 1990)

(untitled) - Kaupp, G.; Reza Naimi-Jamal, M.; Schmeyers, J. (Tetrahedron, 2003)

(untitled) - Wada, S.; Suzuki, H. (Tetrahedron Lett., 2003)

(untitled) - Trotzki, R.; Hoffmann, M. M.; Ondruschka, B. (Green Chem., 2008)

(untitled) - Batzdorf, L.; Fischer, F.; Wilke, M.; Wenzel, K.-J.; Emmerling, F. (Angew. Chem., Int. Ed., 2015)

(untitled) - Kulla, H.; Wilke, M.; Fischer, F.; Röllig, M.; Maierhofer, C.; Emmerling, F. (Chem. Commun., 2017)

(untitled) - Chang, M.-J.; Fang, T.-C.; Tsai, H.-Y.; Luo, M.-H.; Chen, K.-Y. (Acta Crystallogr., Sect. E, 2012)

(untitled) - Paris, O.; Li, C.; Siegel, S.; Weseloh, G.; Emmerling, F.; Riesemeier, H.; Erko, A.; Fratzl, P. (J. Appl. Crystallogr., 2007)

(untitled) - Hammersley, A. P.; Svensson, S. O.; Hanfland, M.; Fitch, A. N.; Hausermann, D. (High Pressure Res., 1996)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Crystallogr., 2008)